Vaginal Impact of the Oral Administration of Total Freeze-Dried Culture of LCR 35 in Healthy Women - J. M. Bohbot; J. M. Cardot (Hindawi Limited, 2012)
The use of probiotics in the prevention or treatment of some vaginal infections has been the subject of numerous studies. To assess the presence of Lactobacillus casei rhamnosus (LCR35) in the vagina after an oral administration, an open randomised pilot study was conducted on 20 healthy women of child-bearing age. Materials and Methods. 2 groups of 10 women were given a 28-day oral course, that is, at least 108 CFU/day (group 1) or 2×108 CFU/day (group 2) of LCR35. Nugent score and vaginal screening for LCR35 were undertaken before and after 28 days of treatment. Results. The mean Nugent score decreased in group 1 (−0,2) as well as in group 2 (−0,3). 10% of women in group 1 versus 40% of women in group 2 were carrying LCR35 at the end of the trial. Conclusion. LCR35, at the minimal dose of 2 × 108 CFU/day, can return the Nugent score to normal in healthy women of child-bearing age, by means of a well-tolerated vaginal temporary presence. Phase III clinical trials will specify the preventive or curative impact of this orally administered strain on a range of vaginal disorders such as bacterial vaginosis or vulvovaginal candidiasis.